Organic Waste Utilization for Maggot Breeding to Enhance Economic Welfare in RW 07 Ciparigi Indah - Budi Setiawan; Muanas Muanas; Septian Cahyadi; Julius Taslim; Amanda Marsha Andinna (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Maggots, the larvae of the Black Soldier Fly (BSF), play a crucial role in addressing food waste issues by rapidly and efficiently breaking down organic waste, reducing the volume of waste sent to landfills, and producing high-protein animal feed. Utilizing maggots helps solve environmental problems caused by food waste while providing economic benefits to the community. The community service activity conducted by the Institut Bisnis dan Informatika Kesatuan team focuses on using organic waste for maggot breeding to enhance economic welfare in RW 07 Ciparigi Indah, Bogor. This initiative has had a significant positive impact. In terms of management, the activity has increased community awareness of the maggot breeding cycle through provided guidance. In marketing, the operators have gained skills in using digital technology for marketing strategies and creating a financial reporting system application to assist with financial management. The activity has increased the supply of organic waste used as maggot feed in production. The provision of appropriate technology has led to a significant rise in maggot production.